Political Economy of the Gulf Sovereign Wealth Funds : a Case Study of Iran, Kuwait, Saudi Arabia and the United Arab Emirates. - Bazoobandi, Sara (Routledge studies in Middle Eastern economies., 2012)
Using four Gulf sovereign wealth funds as case studies - Iran, Kuwait, Saudi Arabia and the UAE - this book examines and analyses the history, governance and structure, and investment strategies of the above mentioned funds, in the context of on-going debates about their transparency. The book discusses how most Gulf sovereign wealth funds were established under colonial rule, and have operated in the global financial system for many decades. With the increase of oil revenues, it goes on to look at how the funds have broadened their asset classes and their institutional development. D.